THE DETERMINANT OF THE INCIDENT OF HYPERTENSION IN BALEKAMBANG HELATH CENTER, BENDUNGAN VILLAGE, JONGGOL SUB - DISTRIC, IN THE YEAR 2021 (Jurnal Mitra Kesehatan, 2021)
Introduction: Hypertension is a condition of high blood pressure and as The Silent Killer because most are asymptomatic or asymptomatic. sethat treatment is often too late. The incidence of hypertension is influenced by several factors, such as obesity (obesity), alcohol consumption, sodium intake, and stress. The purpose of this research is to find outdeterminants of the incidence of hypertension in Balekambang Health Center. Method: This type of research is analytic observational using a cross sectional research design. The sampling technique used in this study is Probability Sampling with Simple Random Sampling with a total sample of 86 respondents using the chi square test. Results: The results of this study are the majority of the respondents' ages are included in the early elderly, namely the age of 46-55 years (26.7%), the most gender is female (61.6%) and the majority have low education (65.1%), the majority of respondents do not experience obesity (76.7%), the majority of respondents do not consume alcohol (81.4%), more respondents have high sodium intake (59.3%) and the majority of respondents experience stress (51.2%). Conclusion: The conclusion of this study obtained that the factors associated with the incidence of hypertension are overweight/obesity (p-value = 0.001), sodium intake (p-value = 0.001), and stress (p-value = 0.001). Meanwhile, there is no relationship between the incidence of hypertension and alcohol consumption (p-value = 0.055). Health services can improve health promotion efforts regarding prevention of hypertension cases through education to overcome obesity, alcohol consumption, high sodium intake and stress.